Empowering the Creative Economy through Digital Branding and E-Commerce Optimization for KWT Bunga Telang in Tegal Ratu Village - Wijaya, Ferdian Bangkit; Budiaji, Weksi; Arina, Faula; Sonda, Atia; Mahuda, Isnaini; Abdullah, Syarif; Utami, Sofi Cahya; Wirantara, Syahtriandi (Journal of Community Service in Science and Engineering (JoCSE), 2026)
Community service is a fundamental pillar of higher education aimed at transforming academic research into practical solutions for societal empowerment. This community service program focuses on the KWT Bunga Telang in Tegal Ratu Village, Cilegon, which faces significant hurdles in digital transformation despite having high-potential herbal products. Using a participatory approach, this program implemented a comprehensive strategy involving upstream production standardization, visual branding restructuring, and downstream digital marketing optimization. The concrete outputs of this program include standardized professional packaging designs, a curated digital product catalog, and a verified e-commerce presence on the Shopee platform. Results from pre-test and post-test evaluations indicated a significant increase in the partners' cognitive and practical mastery, rising from an average of 42% to 88%, with a mean difference of 46%. This intervention effectively shifted the group’s operations from traditional, limited local sales to a broader digital market reach, lowering psychological barriers toward technology adoption and establishing a robust digital presence for local herbal products. The synergy between academia and local stakeholders proved essential in accelerating economic independence for women-led micro-enterprises.